Vocational Learning Management for Students with Special Needs: A POACE-Based Case Study at SLB Negeri 1 Padang - Chania Waty; Yuliana; Weni Nelmira; Giatman (Jurnal Penelitian Pendidikan IPA, 2025)
This study analyzes the management of vocational learning for students with special needs at SLB Negeri 1 Padang by applying the POACE framework: Planning, Organizing, Actuating, Controlling, and Evaluating. The research addresses the problem of inconsistent learning management and limited alignment between vocational programs and students’ functional needs. Using a qualitative descriptive design, data were collected through in-depth interviews, classroom observations, and document analysis involving school leaders, vocational teachers, and students. The data were analyzed through Miles and Huberman’s interactive model: data reduction, data display, and conclusion drawing. The results show that the implementation of POACE is present but uneven. Planning is not yet based on comprehensive student assessments; organizing is hindered by mismatches between teacher expertise and assigned tasks; actuating is limited by insufficient adaptive learning resources; controlling lacks structured monitoring instruments; and evaluation does not include competency measurement or pathways to employment readiness. Overall, the study concludes that vocational learning management requires more systematic, data-driven, and inclusive strategies. Strengthening each POACE component is essential to improving the relevance and effectiveness of vocational education for students with special needs.